2009
DOI: 10.1002/eji.200838403
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between DC and Plasmodium berghei/chabaudi‐infected erythrocytes in mice involves direct cell‐to‐cell contact, internalization and TLR

Abstract: Early interactions between blood-stage Plasmodium parasites and cells of the innate immune system are very important in shaping the adaptive immune response to malaria, and a number of studies have suggested that DC are responsible for this phenomenon. Therefore, we examined the capacity of murine BM-derived DC to internalize parasites, be activated and produce cytokines upon in vitro interaction with murine erythrocytes infected with two different strains of rodent malaria parasites (Plasmodium berghei and Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 53 publications
(59 reference statements)
3
32
2
4
Order By: Relevance
“…Activation of NF-kB and MAPK signaling pathways has been demonstrated in response to a number of Plasmodium-derived factors including GPI (23), hemozoin (22), and pRBCs (24,25). Consistently, we found that both NF-kB and MAPK signaling pathways were upregulated in pRBC-stimulated BMDMs (Fig.…”
Section: Caspase-12 Dampens Parasite Clearance By Inhibiting Nf-kb Sisupporting
confidence: 86%
See 1 more Smart Citation
“…Activation of NF-kB and MAPK signaling pathways has been demonstrated in response to a number of Plasmodium-derived factors including GPI (23), hemozoin (22), and pRBCs (24,25). Consistently, we found that both NF-kB and MAPK signaling pathways were upregulated in pRBC-stimulated BMDMs (Fig.…”
Section: Caspase-12 Dampens Parasite Clearance By Inhibiting Nf-kb Sisupporting
confidence: 86%
“…A critical regulator of cytokine-mediated cellular responses, NF-kB is activated downstream of a number of proinflammatory pathways and has been shown to be activated by in vitro exposure to Plasmodium-derived products (22)(23)(24)(25). Here we show NF-kB activation by P. chabaudi both in vitro and in vivo, which, in both cases, is enhanced in the context of caspase-12 deficiency.…”
Section: Discussionmentioning
confidence: 57%
“…Because the molecular pathways underlying IFN-g-induced priming involve the activation of TLRs and other IFN-inducible genes (18), we compared the expression of tlr2, tlr4, tlr9, md2, cd36, il1b, stat3, irf7, and ifnar mRNAs in splenic DCs. This population is located in the red pulp of the spleen, where it is in direct contact with iRBCs, and also in the white pulp, contributing to both parasite clearance and T cell activation (27,28). We observed a significant increase in the expression of these mRNAs in DCs from mice 60d , with the exception of ifnar mRNA, whereas there was no difference between mice 200d and the AMCs (Fig.…”
Section: Ifn-g-induced Priming Of the Innate Immune System Subsides Amentioning
confidence: 71%
“…Considering the existence of several TLR ligands in Plasmodium, such as the GPI anchor, which is recognized by the TLR2/TLR1 complex with the contribution of TLR4 (31,32), and parasite DNA, which is recognized by TLR9 (33), the long-lasting TLR hyperresponsiveness in chronic mice maintains the capacity of macrophages, DCs, and other TLR-bearing cells to recognize iRBCs and merozoites. In fact, it has been shown that DC activation not only requires direct cell-to-cell contact and internalization of iRBCs by DCs but also involves TLR4, TLR9, MyD88, and signaling via NF-kB (27). Moreover, TLR3 and TLR9 promote bacterial uptake by murine and human macrophages through the induction of a phagocytic gene program, which also is induced by TLR4 and TLR5 (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the polarization of Th1/Th2 immune responses will determine malarial fatalities (Hansen, Siomos et al 2003). In a mouse model utilized by Seixas et al, DCs are activated in response to pRBCs internalization, and are important in shaping the adaptive immune response to severe malaria (Seixas, Moura Nunes et al 2009). …”
Section: Immunity To Malariamentioning
confidence: 99%